2022
DOI: 10.1038/s41598-022-24266-7
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic accuracy study on an innovative auto-edge detection technique for identifying simulated implant fractures on radiographic images

Abstract: Implant fracture is a rare but devastating complication of treatment in partially or fully edentulous patients which requires prompt diagnosis. Nevertheless, studies on defining the most accurate technique for the detection of implant fractures are lacking. In the present study, the Canny edge detection algorithm was applied on multiple radiographic modalities including parallel periapical (PPA), oblique periapical (OPA), and cone beam CT (CBCT) with and without metal artifact reduction (MAR) to examine its ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Three parameters of the Canny algorithm including standard deviation of the Gaussian filter, high and low sensitivity thresholds can be set manually by the operator. Previous studies have suggested certain values for these three parameters to achieve the best image quality 15 , 17 . In this study, two experienced oral and maxillofacial radiologists who were not among the observers viewed the images to confirm that the suggested values for the aforementioned parameters provided the finest image details.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three parameters of the Canny algorithm including standard deviation of the Gaussian filter, high and low sensitivity thresholds can be set manually by the operator. Previous studies have suggested certain values for these three parameters to achieve the best image quality 15 , 17 . In this study, two experienced oral and maxillofacial radiologists who were not among the observers viewed the images to confirm that the suggested values for the aforementioned parameters provided the finest image details.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous studies, CBCT scans using a 0.3 mm voxel size would demonstrate root resorption with high accuracy 14 . Nevertheless, streaking artifacts generated from high-density materials such as intracanal posts and metallic restorations could corrupt the CBCT data by disfiguring the anatomical structures 15 23 . Such artifacts could jeopardize the diagnosis of lesions such as ECR especially when they are small and therefore postpone their treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation